Pregnancy-Related RBC Alloimmunization in Sickle Cell Trait Patients; A Single-Center Experience. (28th October 2020) - Barouqa, Mohammad; Castrodad-Rodriguez, Carlos; Gil, Morayma Reyes; Nelson, Randin; Szymanski, James; Paroder, Monika
Abstract: Background: Sickle Cell Disease (SCD) is an autosomal recessive disorder, which results from a point mutation in the Î²-globin gene. The production of mutant Hb S (V6E) leads to hemolytic anemia and numerous clinical complications. Patients homozygous for HbS gene (SS) typically rely on life-long transfusion therapy. Alloimmunization to foreign RBC antigens in multiply transfused patients is significantly more frequent in SS patients (observed in 7–47%) compared to patients with HbA (AA), and can pose a significant hurdle in finding compatible RBCs. However, the mechanism for enhanced alloimmunization in SS patients has not yet been elucidated. Patients heterozygous for HbS (SA) have a no distinct clinical phenotype and do not typically require transfusions. We investigated the rate of RBC antigen alloimmunization and specificity in SA patients. Aim: The aim of this study was to determine and compare the rate and specificities of RBC antigen pregnancy-related alloimmunization in SA and AA patients. Methods: In our retrospective study, we identified females who delivered a newborn between January 2014 to October 2019, for whom prenatal hemoglobin electrophoresis testing, and prenatal and perinatal antibody screening and identification was performed. R (V.3.6.2) statistical computing program was used for analysis. Results: A total of 41735 subjects were identified: 40058 (AA) and 1677 (SA). African Americans were more prevalent in the SA compared to the AA group (55.8% vs 29.4%, P<0.01)and were more likely to have received ≥ 1 transfusion during pregnancy (4.5% vs 3.3%, P<0.01). A total number of 267 alloantibodies were detected in 246 patients (0.6% of the studied population) during pregnancy, 228 patients (0.6%) in the AA group and 18 patients (1.1%) in the SA group.229/246 (93%) of patients with antibodies did not receive transfusion during pregnancy, and thus antibodies were considered to represent pregnancy-related alloimmunization. In non-transfused subjects the SA group were more likely to have developed alloantibodies in pregnancy compared to the AA group [OR= 1.94, P=0.015]. The median age of patients with antibodies in the SA was older [33.5 vs 27 (p=0.008)] as compared to those in the AA group [29 vs 27 (p=0.002)]. The most common antibody identified was anti-E (SA 42% vs AA 28%), anti-Lea (SA 21% vs AA 13%) and anti-C (SA 5% vs AA 12%). Subjects with pre-existing alloantibodies had a 5.4x increased risk of forming a new allo-antibody. However only 0.1% of subjects had a history of prior allo-antibodies, with no significant difference identified between AA and SA. Conclusions: SA patients were found to have an increased rate of pregnancy-related alloimmunization (OR 1.75, P=0.02) after adjusting for the effects of increasing age, RH type, ethnicity, number of previously existing antibodies and number of transfusions in pregnancy.